The new cottage facility in Vienna - Borkowski, Carl von, 1829-1905 (architect):::Creator:::::::::::: (2020)
Reproduction of an engraving based on a drawing of the cottages built in the Währing suburb of Vienna in the late 19th century, designed by architect Carl von Borkowski.